Pengaruh Pemanfaatan Teknologi, Iklim Kelas dan Task commitment Terhadap Hasil Belajar Ekonomi: The Influence of Technology Utilization, Classroom Climate, and Task Commitment on Economics Learning Outcomes - Bela, Najma Fauzia; Solihat, Ai Nur; Gumilar, Gugum (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This research is motivated by the low academic performance of students in the Economics subject in the 11th grade at SMAN 1 Singaparna. This study aims to determine the effect of technology utilization, classroom climate, and task commitment on students' learning outcomes. The use of technology referred to in this study is Gadgets. This research falls under quantitative research using survey methods and explanatory design. The population in this study consists of all 11th-grade students at SMAN 1 Singaparna for the 2024/2025 academic year who are studying economics, totaling 215 students. The sampling technique used was the saturated sampling technique, so the entire population was made the sample in the study. Data were obtained through the distribution of questionnaires and documentation, then analyzed using multiple linear regression analysis with the help of SPSS version 27. The research results show that there is a positive and significant influence between the utilization of technology, classroom climate, and task commitment on student learning outcomes, both partially and simultaneously. Furthermore, these three variables simultaneously affect learning outcomes with an F_calculated value greater than the F_table value, specifically F_calculated 163.5 > 2.65, indicating a strong and significant relationship. The conclusion of this study is that the utilization of technology, classroom climate, and task commitment collectively influence students' learning outcomes in Economics at SMAN 1 Singaparna.